Impact of Extension Activities of Krishi Vigyan Kendra, Jodhpur on Knowledge Level of Farmers on Improved Agricultural Production Practices - Singhal, Savita; Vatta, Lalita; Kalash, Poonan; Sharma, S K (Annals of Arid Zone, 2018)
The present investigation was undertaken in Jodhpur district of Rajasthan. A multi-stage sampling design was used to select the sample farmers as respondents. A total of 180 farmers were selected for the study purpose. The primary data for the study were collected from respondents through specially prepared interview schedule. It was found that nearly 92% beneficiary respondents had high to medium level of knowledge about improved agricultural production technologies, while, only 7.50% of the beneficiary respondents possessed low level of knowledge. In case of non-beneficiary respondents, majority of the farmers (43%) had medium level of knowledge of improved technologies and the percentage of those possessing low knowledge was 45%. Non-beneficiary respondents seem to have the least level of knowledge as is evident from the lowest number of farmers having high knowledge and high number in the category of low to medium knowledge.Key words: Impact, extension activities, KVK, production practices